Development of Inductive Quarter Wave Radio Frequency Coaxial Resonant Cavity for a Compressed Natural Gas Ignition - Nissirat, Liyth Ahmad (2006)
The function of the ignition systems is to inject the required energy into the combustion chamber in order to ignite the air-fuel mixture. The amount of the injected energy depends on many factors such as the kind of combustion gas used, air-fuel ratio, and the combustion pressure. To meet the future fuel economy demands the vehicle engine manufacturers try to design engines that run on lean or ultra lean air-fuel ratios. These lean mixtures require more efficient energy injection mechanism to be ignited.